2021
DOI: 10.1007/s00268-021-06265-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor Burden Score on Conditional Survival after Curative‐Intent Resection for Hepatocellular Carcinoma: A Multi‐Institutional Analysis

Abstract: Background The impact of tumor burden score (TBS) on conditional survival (CS) among patients undergoing curative-intent resection of hepatocellular carcinoma (HCC) has not been examined to date. Methods Patients who underwent liver resection of HCC between 2000 and 2017 were identified from a multiinstitutional database. The impact of TBS and other clinicopathologic factors on 3-year conditional survival (CS 3 ) was examined. Results Among 1,040 patients, 263 (25.3%) patients had low TBS, 668 (64.2%) had medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Currently, surgery is considered the best candidate therapy for patients with solitary HCC, while the prognostic staging of HCC following curative hepatectomy remains a challenge; although several staging systems have been proposed, none have been universally adopted, since HCC is heterogeneous and is influenced by tumor burden ( 11 ), viral infections ( 12 ), liver function ( 13 ), immune response ( 14 ) and metabolic abnormalities ( 15 ). An ideal prognostic model for risk stratification needs to be developed with appropriate methods.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surgery is considered the best candidate therapy for patients with solitary HCC, while the prognostic staging of HCC following curative hepatectomy remains a challenge; although several staging systems have been proposed, none have been universally adopted, since HCC is heterogeneous and is influenced by tumor burden ( 11 ), viral infections ( 12 ), liver function ( 13 ), immune response ( 14 ) and metabolic abnormalities ( 15 ). An ideal prognostic model for risk stratification needs to be developed with appropriate methods.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally based solely on factors obtained at the time of diagnosis/surgery, standard survival estimates rely on static rather than dynamic measures of long-term survival. 8,9 In addition, survival estimates often aggregate data into prognostic groups, which may be helpful for the general prediction of survival, but may not be as applicable to determine the prognosis of an individual patient. 10 In particular, although they are a powerful tool, survival analyses also are vulnerable to a number of biases, which can lead to biased conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…6 Multiple studies have reported changes over time in the CS of patients undergoing resection for HCC. [7][8][9][10] However, only one study reported the CS of patients undergoing RFA for HCC. 7 It enrolled patients with Child-Pugh class B liver disease.…”
Section: Introductionmentioning
confidence: 99%